2007
DOI: 10.1515/bc.2007.154
|View full text |Cite
|
Sign up to set email alerts
|

Association of cathepsin E with tumor growth arrest through angiogenesis inhibition and enhanced immune responses

Abstract: Cathepsin E (CE) is an intracellular aspartic proteinase implicated in various physiological and pathological processes, yet its actual roles in vivo remain elusive. To assess the physiological significance of CE expression in tumor cells, human CE was stably expressed in human prostate carcinoma ALVA101 cells expressing very little CE activity. Tumor growth in nude mice with xenografted ALVA101/hCE cells was slower than with control ALVA101/mock cells. Angiogenesis antibody array and ELISA assay showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Cleavage of plasminogen by MMP2, MMP3, MMP7, MMP9, MMP12, and MMP19 generates angiostatin (Patterson and Sang 1997;Cornelius et al 1998;Lijnen et al 1998;Moses and O'Reilly 2003;Brauer et al 2011), and endostatin is generated through cleavage of collagen XVIII by MMP3, MMP9, and MMP13 (Ma et al 2007;Bendrik et al 2010;Fukuda et al 2011). Besides MMPs, different cathepsin family members, including the cysteine cathepsins L and S (Felbor et al 2000;Veillard et al 2011) and the aspartic cathepsin E (Shin et al 2007), have been shown to generate endostatin from collagen XVIII. Conversely, Wang et al (2006) proposed that cathepsin S promotes angiogenesis by degradation of the anti-angiogenic peptides canstatin and arresten and generation of proangiogenic fragments from laminin 5 in pancreatic neuroendocrine cancer (Fig.…”
Section: Angiogenesismentioning
confidence: 99%
“…Cleavage of plasminogen by MMP2, MMP3, MMP7, MMP9, MMP12, and MMP19 generates angiostatin (Patterson and Sang 1997;Cornelius et al 1998;Lijnen et al 1998;Moses and O'Reilly 2003;Brauer et al 2011), and endostatin is generated through cleavage of collagen XVIII by MMP3, MMP9, and MMP13 (Ma et al 2007;Bendrik et al 2010;Fukuda et al 2011). Besides MMPs, different cathepsin family members, including the cysteine cathepsins L and S (Felbor et al 2000;Veillard et al 2011) and the aspartic cathepsin E (Shin et al 2007), have been shown to generate endostatin from collagen XVIII. Conversely, Wang et al (2006) proposed that cathepsin S promotes angiogenesis by degradation of the anti-angiogenic peptides canstatin and arresten and generation of proangiogenic fragments from laminin 5 in pancreatic neuroendocrine cancer (Fig.…”
Section: Angiogenesismentioning
confidence: 99%
“…Cathepsin E www.fhc.viamedica.pl inhibits growth of the tumor and inhibits apoptosis in prostate cancer cells by releasing tumor necrosis factor [75]. Furthermore, inhibition of tumor growth by inhibition of angiogenesis, as well as strengthening immunological response, has been found [76]. An increased activity of cathepsin E in tumors causes increased expression of certain anti-angiogenic factors, including interleukin-12 and endostatin.…”
Section: The Role Of Cathepsin E In Pathobiochemistrymentioning
confidence: 99%
“…Furthermore, proteolytic events affect tumor biological processes, such as proliferation and angiogenesis, by liberating ECM-bound growth and angiogenic factors or by processing and activating these factors (3,4). Several protease classes, including metallo-, aspartic, serine, and cysteine proteases, are implicated in promoting tumor progression and metastasis (5)(6)(7)(8). The family of lysosomal cysteine proteases, the cysteine cathepsins (clan CA; C1 family), has recently attracted attention as tumor-promoting enzymes (9).…”
mentioning
confidence: 99%